An extreme-sib-pair genome scan for genes regulating blood pressure. - Xu, X (1999)
Hypertension, a risk factor for many cardiovascular, cerebrovascular, and renal diseases, affects one in four Americans, at an annual cost of>$30 billion. Although genetic mutations have been identified in rare forms of hypertension, including Liddle syndrome and glucocorticoid-remediable aldosteronism, the abundance of plausible candidate genes and potential environmental risk factors has complicated the genetic dissection of more prevalent essential hypertension. To search systematically for chromosomal regions containing genes that regulate blood pressure, we scanned the entire autosomal genome by using 367 polymorphic markers. Our study population, selected from a blood-pressure screen of >200,000 Chinese adults, comprises rare but highly efficient extreme sib pairs (207 discordant, 258 high concordant, and 99 low concordant) and all but a single parent of these sibs. By virtue of the sampling design, the number of sib pairs, and the availability of genotyped parents, this study represents one of the most powerful of its kind. Although no regions achieved a 5% genomewide significance level, maximum LOD-score values were >2.0 (unadjusted P<.001) for regions containing five markers (D3S2387, D11S2019, D15S657, D16S3396, and D17S1303), in our primary analysis. Other promising regions identified through secondary analyses include loci near D4S3248, D7S2195, D10S1423, D20S470, D20S482, D21S2052, PAH, and AGT.